Selectivity filters and cysteine-rich extracellular loops in voltage-gated sodium, calcium, and NALCN channels - Stephens, Robert F.; Guan, W.; Zhorov, Boris S.; Spafford, J. David (Frontiers in Physiology, 2015)
How nature discriminates sodium from calcium ions in eukaryotic channel pores has been difficult to resolve because these are asymmetrical pores, contributed by four different homologous domains. Alternatively spliced pores in invertebrate homologs provide insights into different structural features underlying calcium and sodium selectivity. NALCN generates alternative ion selectivity with splicing that changes the high field strength (HFS) site at the narrowest juncture of the hourglass shaped pore selectivity filter. NALCN splices in a HFS site that resembles calcium channels with a ring of glutamates contributed by all four domains (EEEE) like in highly calcium selective Cav1 or Cav2 channels, or splices in a lysine (K) residue in the third or second position (EEKE or EKEE) resembling the sodium selective channels that have primarily either DEKA or DKEA HF sites. Alternative splicing to regulate sodium and calcium ion selectivity in T-type channels involves alternative tri- and penta-cysteine extracellular turrets (S5P) of different lengths. Extracellular turrets of increasing lengths in potassium channels (KIR2.2, hERG, and K2P1) contribute to a changing landscape above the pore selectivity filter that can limit drug access and serve as an ion pre-filter before ions reach the pore selectivity filter below. T-type channels have an infusion of 4 to 12 extra cysteines in extracellular regions above a core eight cysteines found in most eukaryotic channels. The pattern of conservation suggest a possible pairing of long turrets in Domains I and III, which are bridged with core cysteines in NALCN, Cav, and Nav channels, and pairing of shorter turrets in Domains II and IV in T-type channel through disulfide bonds involving specific cysteines. Pairing of extended turrets likely contribute to the large extracellular domain as seen in single particle electron cryo-microscopy images in representative 4x6TM channels.